Rancang Bangun Turbin Angin Darrieus 3 Sudu Skala Lab - Akbar Teguh Prakoso; M. Alif Abiyyu; Dendy Adanta (Universitas Sriwijaya, 2023)
This research aims to design and build a Darrieus wind turbine with three blades on a laboratory scale. The Darrieus wind turbine was chosen because of its efficient design in utilizing wind speed to produce mechanical energy. The research methodology involves several stages, starting from designing turbine blades that use PVC pipes that are heated and formed into flat plates, to designing turbine frames from hollow iron and iron plates. The blade and frame design is optimized to ensure stable and efficient turbine rotation. The turbine is equipped with a washing machine dynamo to increase rotational stability compared to using a fillow block. The research results show that the Darrieus turbine design with three blades is capable of producing stable and efficient rotation. The rotation speed of the turbine is influenced by wind speed, blade area, and blade curve length. Apart from that, the height between the frame and blades also affects the stability of the rotation. The design calculation results show that the turbine sweep area is 24617 m² with a wind speed of 3 m/s resulting in a tip speed ratio of 5 and a turbine rotation speed of 15 m/s. The conclusion of this research is that the Darrieus wind turbine with three blades can function well on a laboratory scale. Proper blade and frame design is critical to achieving stable and efficient rotation. This turbine has the potential to be further developed as a renewable energy solution in Indonesia.